From bedside to bench: how existing therapies inform the relationship between Epstein–Barr virus and multiple sclerosis. Issue 2 (23rd February 2023) - Dyer, Zoe; Tscharke, David; Sutton, Ian; Massey, Jennifer
Abstract: Therapy for relapsing–remitting multiple sclerosis (MS) has advanced dramatically despite incomplete understanding of the cause of the condition. Current treatment involves inducing broad effects on immune cell populations with consequent off‐target side effects, and no treatment can completely prevent disability progression. Further therapeutic advancement will require a better understanding of the pathobiology of MS. Interest in the role of Epstein–Barr virus (EBV) in multiple sclerosis has intensified based on strong epidemiological evidence of an association between EBV seroprevalence and MS. Hypotheses proposed to explain the biological relationship between EBV and MS include molecular mimicry, EBV immortalised autoreactive B cells and infection of glial cells by EBV. Examining the interaction between EBV and immunotherapies that have demonstrated efficacy in MS offers clues to the validity of these hypotheses. The efficacy of B cell depleting therapies could be consistent with a hypothesis that EBV‐infected B cells drive MS; however, loss of T cell control of B cells does not exacerbate MS. A number of MS therapies invoke change in EBV‐specific T cell populations, but pathogenic EBV‐specific T cells with cross‐reactivity to CNS antigen have not been identified. Immune reconstitution therapies induce EBV viraemia and expansion of EBV‐specific T cell clones, but this does not correlate with relapse. Much remains unknown regarding the role of EBV in MS pathogenesis. We discuss future translational research that could fill important knowledge gaps. Abstract : Epidemiological evidence supports a potential role for Epstein–Barr Virus (EBV) in multiple sclerosis (MS) pathogenesis. Several hypotheses propose differing roles for EBV in establishing disease, but none have been proven to date. Investigating the effect of immunosuppressive and immune‐modulatory therapies used in MS on immune responses to EBV, EBV reactivation and EBV load offers useful insights into the validity of these hypotheses.